130 Grownish: how and when to include adolescents in adult research. (17th August 2022) - Bucci-Rechtweg, Christina; Edwards, Martin; Turner-Thomas, Rhian; Siapkara, Angelika; Gamalo, Margaret; Norjavaara, Ensio; Haack, Kristina An; Koukougianni, Menia
Abstract : Aims: Trial protocols routinely exclude adolescents from enrolment in adult trials as 18 years is used as the minimum age eligibility criterion. Due to perceived vulnerability, trials for paediatric patients (children and/or adolescents) are often delayed until after the adult development has demonstrated a positive benefit-risk, relegating paediatric research until after a medicine is authorized for adult use. This approach stems from ethical debates that children must be further protected from unnecessary risks of harm. Across regional jurisdictions, adolescence is typically determined utilizing chronological age, often reflecting the legal age of majority in that region. Globally, the legal definition of adolescence roughly corresponds with the period of time between the ages of 10 and 20 years of life. Adolescence, however, is a period of development characterized by sexual maturation, a variable and accelerated rate of growth and continued neurocognitive development. Methods: We evaluated regional and international regulatory guidance and statute for their definition of the adolescent population. In addition to the legal age of majority, we identified two key thematic categories that underscore the adolescent definitions utilized globally - behavioral and developmental/physiological. Leveraging these themes, the research team developed a user-friendly adolescent inclusion decision-tree for use by sponsors, investigators, ethics committees, and reviewing health agencies as they evaluate study protocols. The tool combines a series of considerations that evaluate developmental, therapeutic and disease-related characteristics as a more relevant scientific basis than age alone to inform the appropriateness of adolescent cohorts in adult research. The tool guides users to evaluate seven key as a means to facilitate robust consideration of the role for adolescent inclusion in adult research. These topics include: Disease Product Statistical Operational Investigator & Site-focused Sponsor-focused Legal & Ethical Results: Beta-testing of the tool was launched in January 2022. Testers (academia researchers, coordinators, industry, ethics committee members) have been asked to evaluate each topic section on its unique merits and to assess the tool comprehensively on whether the sections address all elements crucial to age-inclusive research. The objective is to assess the tool for its: 1. Functionality (how 'useful' is the tool in your role?) 2. Interpretability (how 'understandable' is each component of the tool?) 3. Usability (how 'easy' is the tool to use?) Identification of gaps (critical errors of omission) are also intended to be captured. Insights gained during beta-testing will be utilized by the research team to enhance the functionality, interpretability and usability of the adolescent inclusion decision-tree. Conclusion: We encourage trial sponsors, investigators, regulators, and ethics committees to challenge research orthodoxy related to adolescent inclusion in adult research and seek trial solutions grounded in science rather legal definitions of age alone. We developed an adolescent inclusion decision tree to facilitate discourse on trial design considerations that facilitate the more timely inclusion of adolescents in research. Inclusion of adolescents within appropriate adult studies not only facilitates the generation of data for use in determination of benefit-risk in the adolescent population, it can also serve as a meaningful pathway to facilitate earlier access for adolescents to efficacious therapies.